Struktur Tanda dan Makna dalam Jabu bolon Ompung Gumata Sidabalok: Telaah Semiotika Budaya - Simbolon, Nada Christin; Herlina; Sinulingga, Jekmen (Yayasan Sagita Akademia Maju, 2025)
This study aims to examine the cultural symbols embedded in Jabu Bolon Ompung Gumata Sidabalok, a traditional Batak Toba house located in Simanindo Village, Samosir Regency. This traditional house functions not only as a residence but also as a visual representation of the cultural values, social structure, and belief systems of the Batak Toba community. The analysis employs a cultural semiotic approach based on Charles Sanders Peirce’s theory, which classifies signs into icons, indexes, and symbols. The research focuses on the visual forms, symbolic functions, and cultural meanings contained in the architectural structures and gorga ornaments. Elements analyzed include the main pillar (saka tunggal), the roof structure (sagong ni ruma), and various gorga carvings found throughout the exterior and interior parts of the house. A descriptive qualitative method was applied, utilizing field observation, in-depth interviews with cultural figures, and visual documentation. The findings reveal 15 types of gorga, 18 symbolic functions, and 20 cultural meanings. Each architectural element embodies spiritual meaning, ancestral reverence, and social order. This research enhances the academic understanding of Batak Toba cultural heritage and provides significant contributions to semiotic studies and the preservation of traditional Nusantara architecture.